The poetics of prophecy: modern afterlives of a biblical tradition - Raz, Yosefa (Cambridge University Press, 2024)
Since the mid-1700s, poets and scholars have been deeply entangled in the project of reinventing prophecy. Moving between literary and biblical studies, this book reveals how Romantic poetry is linked to modern biblical scholarship's development. On the one hand, scholars, intellectuals, and artists discovered models of strong prophecy in biblical texts, shoring up aesthetic and nationalist ideals, while on the other, poets drew upon a counter-tradition of destabilizing, indeterminate, weak prophetic power. Yosefa Raz considers British and German Romanticism alongside their margins, incorporating Hebrew literature written at the turn of the twentieth century in the Russia Empire. Ultimately she explains the weakness of modern poet-prophets not only as a crisis of secularism but also, strikingly, as part of the instability of the biblical text itself. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.